Hyperprolactinemia and Galactorrhea Associated with Risperidone-Fluoxetine Combination Therapy: A Case Report - Nastaran Kordjazy; Kheirollah Gholami; Elliyeh Ghadrdan (Research Center for Rational Use of Drugs (RCRUD), 2020)
Prolactin is a polypeptide hormone secreted and released by lactotroph cells in the anterior pituitary gland in response to diverse physiological stimuli, principally via the inhibitory action of dopamine and serotonin. This paper describes a 44-year-old woman with depression and obsessive-compulsive disorder (OCD) who called the 13-Aban drug and poison information center (DPIC). She was being treated with fluoxetine (80 mg/day) for 10 months until risperidone was added to her regimen for augmentation therapy (0.5 mg/day). Her symptoms improved within less than two months without significant side effects until she experienced painful bilateral breast discharge along with spotting and menstrual irregularity, besides amenorrhea for the previous 2 cycles and serum prolactin level of 33.7 ng/mL, presenting hyperprolactinemia. After discontinuing risperidone, within two weeks, galactorrhea and breast pain disappeared and amenorrhea resolved. Further prolactin level measurement showed the significant reduction. This neuroendocrine effect observed with very low-dose risperidone plus fluoxetine is apparently exerted through both pharmacokinetic and pharmacodynamic augmentation of this combination therapy.